Real essays for college & grad school - McKinney, Anne, 1948- (Real-resumes series., 2000)
Reviews and ExcerptsWhen you are applying to college or grad school, the essays you are asked to write can count up to 60% in admissions decisions and can influence scholarship offers. This book provides real essays to use as samples, and the book contains real essays used by real people to get into law school, business school, Ph. D. programs, colleges including the Ivy League, as well as graduate schools of all types. Learn the proven techniques used by professional writers in developing essays that give admissions committes what they are looking for. "A picture is worth a thousand words" and.